An introduction to Italian sculpture - Pope-Hennessy, John Wyndham, Sir, 1913-1994; Phaidon Press (London : Phaidon Press, 1996)
The standard introduction to this topic, Pope-Hennessy's text is so thorough it forms the de facto corpus in the field. Each chapter addresses the work of one artist with extensive notes and a general bibliography, also arranged by artist, at the end of each volume. Each work is reproduced in black and white, most with details. [Review, Oberlin Art Library Staff, BQP 9/19/02]
--v. 1. Italian Gothic sculpture -- volume 2. Italian Renaissance sculpture -- volume 3. Italian High Renaissance and Baroque sculpture
Keywords: Sculpture, Italian; Sculpture, Gothic -- Italy; Sculpture, Renaissance -- Italy; Sculpture, Baroque -- Italy